Photoelastic stress analysis in mandibular bone surrounding bar-clip overdenture implants - Mônica Nogueira Pigozzo; Dalva Cruz Laganá; Newton Sesma; Glaís Ferrari de Souza; Alvaro Luiz Ichi (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this in vitro study was to evaluate, using the photoelastic analysis method, the stress distribution in mandibular bone surrounding a bar-clip overdenture when 2 implant angulations were simulated. Two mandibular photoelastic models were manufactured, with 2 implants embedded in the interforaminal region: model 1 - PAPI, a photoelastic analysis model with parallel implants; and model 2 - PAAI, a photoelastic analysis model with angled implants. A bar-clip retention system and an overdenture were positioned over the implants, and loads of 1.0, 2.0 and 3.0 bars were applied. The resultant stresses that developed in the supporting structure were photoelastically monitored and were recorded photographically. The results showed that there were no similarities in the areas of stress among the photoelastic resin models when the angulation of the implants was evaluated. Model 1 - PAPI presented a higher stress concentration at the implant apex, while in model 2 - PAAI, there were higher stress concentrations on the mesial and distal implant faces. Within the limitations of this study, it was concluded that the PAPI photoelastic model demonstrated better stress transfer compared to the PAAI model, since the forces oriented along the axis were better absorbed by the bone.